Stratified sampled equilibrium optimizer for agile earth observation satellite observation tasks scheduling - Galloua, Mohamed Elamine; Li, Shuai; Cui, Jiahao (Computing, 2025)
Metaheuristic algorithms constitute one of the most efficient methods for addressing the Agile Earth Observation Satellite Scheduling Problem (AEOSSP). Hence, exploring the capability of a new metaheuristic algorithm called Equilibrium Optimizer (EO) in this domain, is one of the key contributions of this paper. In this work we aim to analyzes the limitations of the original EO algorithm in addressing the specific requirements of AEOSSP. Specifically, the integer-point data representation within the algorithm population, emerges as a challenge for this subject. In response, a new variant, Stratified Sampling Equilibrium Optimizer (SSEO) is proposed to address these deficiencies. Taking into account the specificity of this field, targeted improvements have been introduced. First, the EO algorithm was adapted to support integer-point representation, ensuring compatibility with the discrete encoding scheme. Second, a stratified sampling mechanism is incorporated to mitigate variable duplication across particles, a critical requirement since the AEOSSP formulation strictly prohibits task repetition within a single schedule. Finally, a stagnation mitigation strategy is introduced, leveraging a tailored Lévy flight mechanism. This mechanism includes a customized Lévy step generation method, designed specifically to align with the characteristics of the AEOSSP. The proposed SSEO algorithm is validated using real-world satellite data and demonstrates superior performance across multiple aspects, including solution quality (fitness), computational efficiency (processing time), and robustness against local optima. The implementation code for the proposed Stratified Sampling Equilibrium Optimizer (SSEO) algorithm is publicly available at: https://github.com/EnimaG/SSEO . Highlights The EO algorithm is modified to support integer-point representation, enabling effective handling of AEOSSP’s discrete encoding requirements. A stratified sampling mechanism is implemented to prevent task duplication across particles, ensuring feasible schedules and improving population diversity. A tailored Lévy flight-based mechanism with adaptive step generation is introduced to mitigate stagnation and enhance exploration.